Analysis of risk concept of breast cancer in women with HIV/AIDS: Walker and Avant's methodological features and adjusted applicability - F. R. Araújo Rodrigues; C. D. Mota Rêgo Viana; G. A. Andrade Cunha; M. L. Duarte Pereira (Universidad de Alicante, 2015)
The objective of this study targets the usage of the concept analysis technique to describe phenomena towards the clarification of the theoretical-practical relationship of constructs applied to nursing. This investigation suggests the identification of previous, following and defining features of the risk concept of breast cancer in women with HIV/AIDS. A broad literature review was conducted from a theoretical-descriptive analysis grounded on the traditional methodology of concept analysis by Walker & Avant (2005). It was possible the identification of previous risks, such as the increasing of chronical-degenerative diseases and the lack of information about healthy lifestyles, as well as the tracking of four risk features (epidemiological risk factors, socio-cultural characteristics, clinical and anatomical features and environmental, occupational and household characteristics) and their indicators. Nevertheless, it was found that to get more effective care it is important to understand the usage of a concept enabling the awareness of changes affecting the indicators through time, as these limit alterations in social, economic, political and sanitary sets.